Islamic Values as Social Glue: Pesantren Strategies in Shaping the Character of Multicultural Students at the Al Hidayah Kudus Islamic Boarding School - Fahrizal Hakim; Eko Sumadi (Tafkir: Interdisciplinary Journal of Islamic Education, 2026)
In the context of Indonesia's ethnically, culturally, and religiously pluralistic society, Islamic boarding schools (pesantren) play a strategic role as religious educational institutions and agents of social integration. The focus of this study is to identify the Islamic values that form the basis for the formation of the social character of Islamic boarding school students (santri) and to examine their internalization strategies in daily life. This study uses a descriptive qualitative approach with data collection techniques through participatory observation, in-depth interviews with kiai, ustadz, and students, and documentation analysis. Data analysis was conducted using the interactive model of Miles and Huberman, which includes data reduction, data presentation, and conclusion drawing. The results show that the dominant Islamic values at the Al Hidayah Kudus Islamic Boarding School are ta'dib (manners), tawasuth (moderation), tasamuh (tolerance), and ukhuwwah (brotherhood), which function as an effective moral and social system in building harmony in the multicultural student environment. Internalization of these values is carried out through three main strategies: the exemplary behavior of kiai and ustadz, socio-religious habits, and strengthening the pesantren culture. The synergy of these three strategies fosters the inclusive, moderate, and empathetic character of students, while strengthening social cohesion among them. This study concludes that Islamic values serve not only as theological teachings but also as social mechanisms capable of integrating diversity into harmony. These findings affirm the role of Islamic boarding schools (pesantren) as a relevant model of Islamic education in strengthening social cohesion in Indonesia's pluralistic society.